UNDERSTANDING ACADEMIC FRAUD IN KUPANG CITY’S ACCOUNTING STUDENTS: INSIGHTS FROM THE FRAUD HEPTAGON MODEL - Aprilio, Hardo; Bahantwelu, Maria Immaculata; Lamaya, Fauziyah (Accounting Department, Politeknik Negeri Bandung, 2025)
The phenomenon of academic fraud has become increasingly prevalent in higher education, including among accounting students who are expected to uphold strong ethical and professional integrity as future auditors, accountants, and financial practitioners. This study examines the influence of the seven dimensions of the Fraud Heptagon—pressure, opportunity, rationalization, capability, arrogance, greed, and ignorance—on academic fraud among accounting students in Kupang City. Using a quantitative-descriptive approach, data were collected from 104 respondents and analyzed using Partial Least Squares (SmartPLS). The results show that only the pressure variable has a significant effect on academic fraud, while the remaining six dimensions do not. These findings indicate that academic pressure is the dominant factor driving dishonest behavior, whereas the collectivistic cultural norms and strong moral values within the Kupang community may suppress the influence of psychological factors such as greed or arrogance. This research contributes to the application of the Fraud Heptagon in accounting education and underscores the need to strengthen ethical formation among future accounting professionals.